Hamartomatous soft tissue tumor: About a case - Cresseri, Aída; Iraola, Maria L.; Trostchansky, José; Carzoglio, Joaquín (Cirugía del Uruguay, 1986)
In view of the presentation of a clinical case of a soft tissue hamartoma, sorne clinical and therapeutics considerations are done. lts rarity is pointed out.